2013
DOI: 10.1021/bm301928u
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Scaffolds to Evaluate Tumor Associated Fibroblast-Mediated Suppression of Breast Tumor Specific T Cells

Abstract: In the tumor microenvironment, the signals from tumor-associated fibroblasts (TAF) that suppress antitumor immunity remain unclear. Here, we develop and investigate an in vitro three-dimensional (3D) scaffold model for the novel evaluation of TAF interaction with breast tumor cells and breast specific, neu antigen (p98) reactive T cells. Breast cancer cells seeded on 3D chitosan-alginate (CA) scaffolds showed productive growth and formed distinct tumor spheroids. Antigen specific p98 T cells, but not naïve T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 26 publications
2
40
0
Order By: Relevance
“…These CA scaffolds can provide the medium for these studies. Additionally, these CA scaffolds can be used to probe the specific microenvironmental cues (cellular and non-cellular [10, 11, 3133]) that promote the conversion of non-CSCs into CSCs to generate effective microenvironmental therapies.…”
Section: Discussionmentioning
confidence: 99%
“…These CA scaffolds can provide the medium for these studies. Additionally, these CA scaffolds can be used to probe the specific microenvironmental cues (cellular and non-cellular [10, 11, 3133]) that promote the conversion of non-CSCs into CSCs to generate effective microenvironmental therapies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a 3D model of mouse mammary carcinoma cells cultured in porous chitosan-alginate scaffolds was used to evaluate CTL function in the presence or absence of tumor-associated fibroblasts. It was found fibroblasts decreased tumor necrosis factor α (TNFα) secretion by CTLs, likely due to elevated production of IL-10 and transforming growth factor beta (TGF-β) in the co-cluture 75 . In another study, drug inhibition of tumor cell-macrophage paracrine interactions was analyzed using co-culture of breast adenocarcinoma cells and macrophages in alginate hydrogel fibers.…”
Section: Biomaterials To Create 3d Tumor Modelsmentioning
confidence: 99%
“…As an example, CAF recruitment and the initiation of fibrosis typically are events associated with the inflammatory response [139]. Being a major component of the tumor stroma, CAFs not only physically impede the penetration of antitumor T cell into the tumor but also modulates immune function via the secretion of numerous cytokines and chemokines [139, 141]. Taking one step further in complexity, Phan-Lai et al developed a tri-culture system to investigate the effect of CAFs on T lymphocyte function in the presence of breast cancer cells [141].…”
Section: Modeling the Complex Tumor Microenvironment In 3dmentioning
confidence: 99%
“…Being a major component of the tumor stroma, CAFs not only physically impede the penetration of antitumor T cell into the tumor but also modulates immune function via the secretion of numerous cytokines and chemokines [139, 141]. Taking one step further in complexity, Phan-Lai et al developed a tri-culture system to investigate the effect of CAFs on T lymphocyte function in the presence of breast cancer cells [141]. Using 3D chitosan-alginate scaffolds for the tri-culture and using TNF-α as a measure of helper T cell activation, it was found that the presence of CAFs impaired the ability of the T cells to secrete TNF-α, highlighting the immunosuppressive role of CAFs in this system.…”
Section: Modeling the Complex Tumor Microenvironment In 3dmentioning
confidence: 99%